Kinerja Pemerintah Gampong Alue Naga dalam Pembangunan Infrastruktur - Nabilah, Shara; Naraseki B, Maura; Yuli Tsabita Chairunnisa, Cut; Yashifa, Namira; Setiawan, Syahrul (Sanger Journal: Social, Administration and Government Review, 2024)
This study evaluates the performance of the Alue Naga Village government, Banda Aceh, in planning, implementing, and evaluating infrastructure development, and identifying supporting and inhibiting factors. This study also provides strategic recommendations to improve the effectiveness and efficiency of development through collaboration with the community and stakeholders. The theoretical basis uses the concept of Bernardin and Rusel's performance with indicators of productivity, service quality, responsiveness, accountability, and responsibility. The method used is descriptive qualitative with data collection through interviews with village officials and the community, direct observation, and analysis of documents such as financial reports and development plans. Data validity is guaranteed through triangulation techniques. The results of the study indicate that community involvement in planning has a positive impact on development. However, there are obstacles in the form of limited budget, weak cross-agency coordination, and lack of community awareness in maintaining facilities.